2007
DOI: 10.1515/epoly.2007.7.1.444
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Behavior of High Density Polyethylene/ZnO Nano-composites

Abstract: High density polyethylene (HDPE)/ZnO composites containing a wide range of ZnO content (1-60 vol%) were prepared by melt compounding. ZnO powders with sizes of ~ 200 nm and ~ 2 μm were employed as reinforcing fillers. The effects of the size and filler particle content as well as annealing treatment on the dielectric and conducting properties of the HDPE/ZnO composites were examined. The results showed that the dielectric constant of HDPE/ZnO composites increased gradually with an increase of the ZnO content. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The results of tensile strength testing demonstrated that size-1 shale composites exhibited higher tensile strength than size-2 and size-3 ones. However, all prepared composites showed tensile strengths superior to those of commonly used insulating materials such as foam glass (0.150 MPa), mineral fiber (0.015 MPa), and polystyrene (0.186 MPa) [35][36][37].…”
Section: Tensile Testingmentioning
confidence: 80%
“…The results of tensile strength testing demonstrated that size-1 shale composites exhibited higher tensile strength than size-2 and size-3 ones. However, all prepared composites showed tensile strengths superior to those of commonly used insulating materials such as foam glass (0.150 MPa), mineral fiber (0.015 MPa), and polystyrene (0.186 MPa) [35][36][37].…”
Section: Tensile Testingmentioning
confidence: 80%
“…In a previous work,35, 36 we found that as ZnO content approached 52 vol %, ZnO particles began to connect each other to form percolating network, which provides a novel surrounding for investigating crystallization behavior of polymers under confinements. In the present work, we report the nonisothermal crystallization kinetics of low‐density polyethylene (LDPE) embedded inside the percolating network of ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 73%
“…While LDPE/60 vol % ZnO exhibits much rough fracture surface consisting of concaves formed by pulling out of ZnO nanoparticles. Such impacted concaves implies that ZnO particles are closely packed in LDPE/60 vol % ZnO and that LDPE is embedded inside ZnO network 35, 36…”
Section: Resultsmentioning
confidence: 99%